2004
DOI: 10.1111/j.1365-2222.2004.01976.x
|View full text |Cite
|
Sign up to set email alerts
|

Cow's milk‐specific immunoglobulin E levels as predictors of clinical reactivity in the follow‐up of the cow's milk allergy infants

Abstract: Monitorization of specific IgE concentration for milk and casein by means of the CAP system in allergic children to CMPs allows us to predict, to a high degree of probability, clinical reactivity. Age factor must be taken into account to evaluate the specific IgE levels which are predictors of tolerance or clinical reactivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
106
2
7

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(125 citation statements)
references
References 11 publications
(15 reference statements)
7
106
2
7
Order By: Relevance
“…Food-specific IgE (FSIgE) levels have been used to predict the outcome of OFC because FSIgE levels above certain cut points were found to be highly predictive of positive OFCs. [5][6][7][8][9][10] However, FSIgE levels are less effective in identifying children who experience a negative OFC. 11 In clinical practice, children with a known food allergy are considered appropriate candidates for OFCs to evaluate for resolution of food allergy when the likelihood of a positive OFC is Յ50%.…”
mentioning
confidence: 99%
“…Food-specific IgE (FSIgE) levels have been used to predict the outcome of OFC because FSIgE levels above certain cut points were found to be highly predictive of positive OFCs. [5][6][7][8][9][10] However, FSIgE levels are less effective in identifying children who experience a negative OFC. 11 In clinical practice, children with a known food allergy are considered appropriate candidates for OFCs to evaluate for resolution of food allergy when the likelihood of a positive OFC is Յ50%.…”
mentioning
confidence: 99%
“…In this clinically different population, the sensitivity of the test decreased to 34 % and a better performance was obtained by using a lower decision point of 15 kU/L (57 % sensitivity, 94 % specificity). In a recent prospective study of a group of children with cow's milk allergy, Garcia-Ara et al 10 showed that the sIgE levels, which were predictors of clinical reactivity, increased with age. This suggests that age must also be taken into consideration when establishing sIgE cutoffs.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of CMA varies with age. CMA is prevalent in early childhood with reported incidences between 2 and 6% [10][11][12] and decreases into adulthood to an incidence of 0.1-0.5% [13][14]. It has been suggested that infants have milk allergies because milk is usually the first source of foreign antigens that they ingest in large quantities, and the infant intestinal system is insufficiently developed to digest and immunologically react to milk proteins.…”
Section: Milk Allergymentioning
confidence: 99%